The Increase of the Gender Wage Gap in Italy during the 2008-2012 Economic Crisis - Daniela Piazzalunga; Maria Laura Di Tommaso (Institute for the Study of Labor (IZA), 2016)
The paper examines the gender wage gap in Italy during the 2008-2012 economic crisis, using cross-sectional EU-SILC data. The gender wage gap increased from 4% in 2008 to 8% in 2012, when for most European countries the gap decreased. After 2010 the growth of the Italian gender wage gap (and its unexplained component) was particularly high in the upper part of the wage distribution. In 2010-11 a wage freeze in the public sector was introduced as an austerity measure: the average public sector premium dropped from 15% to 11%. Using counterfactual analyses, we show that the wage freeze has been one of the major causes of the growth of the gap, disproportionately affecting women, who are more likely to be employed in the public sector. This 'policy effect' accounts for more than 100% of the increase between 2009 and 2011, while other changes, if anything, would have reduced the gap.
Keywords: J31; J71; J16; J45; 330; decomposition; gender wage gap; Great Recession; public sector premium; counterfactual analysis